O konieczności i sposobach współpracy nauczycieli z rodzicami uczniów z niepełnosprawnościami w szkole ogólnodostępnej - wytyczne wynikające z przepisów prawa światowego oraz doświadczeń własnych autorki - Gołubiew-Konieczna, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In her article, the author discusses the need for cooperation between teachers of mainstream schools and parents of students with disabilities. This need results from the complementary roles that teachers and parents play in the education process of children/students with disabilities. The author points out that an individual educational and therapeutic program should be a kind of an agreement between teachers and parents that provides various ways of implementing parents - teachers cooperation. The author also emphasizes the need for teachers to cooperate with the parents of all students in mainstream schools to build inclusive education.
Keywords: nauczyciele; rodzice; współpraca; indywidualny program edukacyjno-terapeutyczny; teachers; parents; cooperation; individual educational and therapeutic program